POTENSI EKSTRAK AQUADES BUNGA KECOMBRANG (Etlingera elatior) SEBAGAI ANTIBAKTERI TERHADAP Escherichia coli DAN Pseudomonas aeruginosa PADA PASIEN INFEKSI SALURAN KEMIH - Yusianti Silviani; Dwi Sri Yuwanndari (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Urinary Tract Infection (UTI) is a common infectious disease, primarily caused by Escherichia coli and Pseudomonas aeruginosa, which are the main UTI-causing bacteria in Indonesia. This study aimed to determine the inhibitory effectiveness of aqueous extract of torch ginger flower (Etlingera elatior) against these bacteria. The extract was obtained through maceration using distilled water as a solvent and tested using the Kirby-Bauer disk diffusion method on bacterial isolates from UTI patient urine samples. Sampling was conducted non-randomly using a quota sampling design with a total of 2 kg of flower sample. The extract concentrations tested were 60%, 70%, 80%, 90%, and 100%, and compared with positive control (ciprofloxacin) and negative control. The results showed that the aqueous extract exhibited inhibitory activity against E. coli and P. aeruginosa, with average inhibition zone diameters ranging from 6–8 mm. Statistical analysis using the Shapiro-Wilk test indicated non-normal data distribution (sig. ≤ 0.001), hence the Kruskal-Wallis test was applied, yielding significance values of 0.003 for E. coli and 0.002 for P. aeruginosa. Further Mann-Whitney test results showed significance values of ≤ 0.05, indicating significant differences between extract concentrations. In conclusion, torch ginger flower extract has potential as a natural antibacterial agent, although its effectiveness is still lower than that of ciprofloxacin.